Observer les pratiques enseignantes : la psychologie historico-culturelle, un cadre pour caractériser les dimensions visibles et invisibles du travail enseignant - Thierry Piot (Recherches en Éducation)
To understand precisely what teachers’work really involves, it is necessary to observe teachers in the classroom notably. To do so, researchers define an approach and a method according to the theoretical framework within which they carry out their research. For over fifty years, a succession of theoretical frameworks and teacher observation methodologies have developed. In this study, research is carried out from the theoretical framework of historic and cultural psychology, which is interesting notably in that it takes into account the two distinct and complementary dimensions of that kind of work: the visible dimension, and the invisible dimension which consists mainly in the cognitive activity of the teacher. As far as methodology is concerned, visible activity is recorded by digital camera, and invisible activity is inferred from explanatory interviews carried out with teachers whose classes are filmed. All this information helps to better understand the complexity of teachers’work, which combines unvarying elements and elements arising from the context and the dynamics of pupil-teacher interactions.